2006
DOI: 10.2478/s11535-006-0030-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alpinia galanga extract on cartilage degradation and on gene expression in human chondrocyte and synovial fibroblast metabolism

Abstract: Abstract:We investigated the effects of A. galanga extract on metabolism and gene expression involved in the interleukin-1β (IL-1β) response of human chondrocyte and synovial fibroblast. A. galanga extract inhibited IL-1β enhanced matrix breakdown of the cartilage explants in a dose-dependent manner. It suppressed uronic acid loss from the tissue and decreased the release of sulfated GAG and hyaluronan into the medium. MMP-2 and MMP-9 activity in the culture medium of chondrosarcomas and synovial fibroblasts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Cells for pellet culture were trypsinized, and the total number of cells was calculated based on a hemocytometer count: 1 × 10 6 cells/pellet, cultured in 1 ml pellet media (DMEM supplemented with 10% FBS and pen/strep which contained 10 7 M dexamethasone, 25 μg/ml L-ascorbate 2-phosphate and 1× ITS 1+). The growth factor pellet media was basic pellet media plus 100 ng/ml IGF-1 and 10 ng/ml TGFβ3 [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cells for pellet culture were trypsinized, and the total number of cells was calculated based on a hemocytometer count: 1 × 10 6 cells/pellet, cultured in 1 ml pellet media (DMEM supplemented with 10% FBS and pen/strep which contained 10 7 M dexamethasone, 25 μg/ml L-ascorbate 2-phosphate and 1× ITS 1+). The growth factor pellet media was basic pellet media plus 100 ng/ml IGF-1 and 10 ng/ml TGFβ3 [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription reaction was performed by using 1.0 µg of total RNA and the RNA was reverse-transcribed into cDNA using RevertAid TM First Strand cDNA synthesis kit (Fermentus Inc, Ontario, Canada). The cDNA was amplified for 35 cycles by using two oligonucleotide primers derived from previously published sequences of MMP -1, -2, -3, -13, IL-1ß, ICE, and GAPDH genes (Pothacharoen et al, 2006). The PCR products were subjected to 1.5% agarose gel electrophoresis.…”
Section: Reverse Transcriptase-polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…The plant's anti-rheumatic actions are attributed to suppressing prostaglandin synthesis through the inhibition of cyclooxygenase-1 and cyclooxygenase-2 (Grzanna et al 2005). Moreover, our previous studies have indicated that A. galanga hexane extract possesses anti-inflammatory effects on IL-1β-induced inflammation in synovial fibroblasts and cartilage explants (Pothacharoen et al 2006). Thus, in this study, we examined the characteristics of Figure 2.…”
mentioning
confidence: 98%